Experienced, trauma-informed teachers working in remote Australia: What is required for their work to be effective? - Brown, Meegan; L’Estrange, Lyra (Frontiers in Education, 2023)
In remote education settings in Australia, experienced teachers who can effectively support students impacted by trauma are essential. Remote communities are unique yet are in many ways vulnerable to trauma as they face higher rates of disadvantage and exposure to traumatic events, including natural disasters and domestic and family violence. This is compounded by a lack of access to effective supports due to the tyranny of distance. Also, First Nations peoples living in remote areas continue to endure the ongoing and traumatic impacts of a violent and disruptive colonization. The qualitative research study detailed in this article explored the requirements for the work of experienced, trauma-informed teachers in remote Australia to be effective. Seven teachers from remote Australia completed a short, online questionnaire and participated in a focus group interview which was analysed using thematic analysis. Three themes emerged from the focus group: (i) preparation of experienced teachers to work in remote settings, (ii) impacts on wellbeing, and (iii) systemic issues. Results showed that for the work of teachers in remote areas to be effective, they need to be prepared well and they need ongoing support and training in trauma-informed practices and cultural awareness. This study contributes important insights into the scope and nature of the work of experienced trauma-informed teachers in remote Australia and recommends ways that education systems can prepare and support teachers so that their work with trauma impacted students is effective.